Extracellular Vesicles Isolated from the Leaf Apoplast Carry Stress-Response Proteins. Issue 1 (8th November 2016) - Rutter, Brian D.; Innes, Roger W.
Abstract : Bacterial infection enhances the production of apoplastic vesicles carrying stress-response proteins in Arabidopsis. Abstract: Exosomes are extracellular vesicles (EV s) that play a central role in intercellular signaling in mammals by transporting proteins and small RNAs. Plants are also known to produce EV s, particularly in response to pathogen infection. The contents of plant EV s have not been analyzed, however, and their function is unknown. Here, we describe a method for purifying EV s from the apoplastic fluids of Arabidopsis ( Arabidopsis thaliana ) leaves. Proteomic analyses of these EV s revealed that they are highly enriched in proteins involved in biotic and abiotic stress responses. Consistent with this finding, EV secretion was enhanced in plants infected with Pseudomonas syringae and in response to treatment with salicylic acid. These findings suggest that EV s may represent an important component of plant immune responses.